Internal mammary node management in breast cancer. A review - Vrana, David; Gatek, Jiri; Cwiertka, Karel; Lukesova, Lucie; Koranda, Pavel (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2013)
BACKGROUND: Internal mammary nodes visualized during sentinel node biopsy for breast cancer, remain an unresolved management issue. Further, both internal mammary node (IMN) radiotherapy and biopsy have attendant risks and hence should be used with caution. The purpose of this review is to highlight the available data and evidence. METHODS AND RESULTS: A PubMed database from 1960 to 2012 using key words: internal mammary nodes, breast cancer radiotherapy planning, adjuvant radiotherapy, sentinel node biopsy in breast cancer and selected publications on the significance of internal mammary nodes in breast cancer treatment, published data and approaches used. We found 14513 relevant papers and we selected 30 that clearly investigated the management of internal mammary nodes during sentinel node search. We focused on the incidence of IMN metastasis (6 papers), risk factors associated with IMN drainage (9 reports), management of IMN and the impact on disease free and overall patient survival (15 papers). CONCLUSIONS: The evidence for breast cancer axillary nodes management is good but the data for other draining nodes such as internal mammary nodes are far less conclusive and further research is needed.
Keywords: nádory prsu; lymfadenektomie; Female; Lymphatic Metastasis; lymfatické metastázy; ženské pohlaví; přežití bez známek nemoci; lidé; Lymph Node Excision; Breast Neoplasms; drenáž; Drainage; Risk Factors; biopsie sentinelové lymfatické uzliny; adjuvantní radioterapie; rizikové faktory; Radiotherapy, Adjuvant; Sentinel Lymph Node Biopsy; Disease-Free Survival; Humans